A Novel Variable Volume Capillary Microgripper for Micromanipulation in Aqueous Media - Enrique Mancha-Sánchez; Andrés J. Serrano-Balbontín; Inés Tejado; Blas M. Vinagre (Micromachines, 2025)
This study presents a novel capillary microgripper for manipulating micrometer-sized objects directly within aqueous environments. The system features dynamic, vision-based feedback control of a non-volatile silicone oil droplet volume, enabling precise adjustment of the capillary bridge force for the adaptable capture of varying object sizes. This approach ensures extended working time and stable operation in water, mitigating the issues associated with evaporation common in other systems. COMSOL Multiphysics simulations analyzed capillary bridge formation. Experimental validation demonstrated successful different object shapes and sizes capture in an aqueous environment and further explored active release strategies necessary due to the non-volatile fluid, confirming the system potential for robust underwater micromanipulation.